2019
DOI: 10.1111/echo.14525
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of transesophageal echocardiography studies rated as rarely appropriate tests for infective endocarditis at an academic medical center

Abstract: Purpose: Endocardial involvement documented by echocardiography is a major criterion of the modified Duke criteria (MDC) for infective endocarditis (IE). Though transesophageal echocardiography (TEE) is sensitive in the diagnosis of IE, it can be inappropriately used.Methods: This retrospective study included all patients who underwent TEE due to bacteremia, fever, and/or endocarditis in a single, tertiary academic medical center in 2013. Data collected from electronic medical charts were as follows: demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, much of the information has been neglected in previous studies. Additionally, some studies [18][19][20][21] examined the role of socioeconomic variables in screening practices; however, these studies were not based on the PDSS questionnaire. Our results are obtained from a tangible pregnancy database based on the PDSS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, much of the information has been neglected in previous studies. Additionally, some studies [18][19][20][21] examined the role of socioeconomic variables in screening practices; however, these studies were not based on the PDSS questionnaire. Our results are obtained from a tangible pregnancy database based on the PDSS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Duggan and Molina [19] studied the differences in socioeconomic variables and knowledge of screening practices and concluded that community-level factors in medically underserved areas may influence screening practices. Amuchastegui and Hur [20] included demographics as a major criterion of improvement to the screening process for infective endocarditis (IE). Chen and Cross [21] found women who lack social support, have an unstable economic status, and those experiencing acculturation were more likely to suffer depression.…”
Section: Pdss Totalmentioning
confidence: 99%
“…In the meantime, it should be available for timely and accurate guidance for the diagnosis and management of IE. As per a single-center study, a considerable number of transesophageal echocardiography (TEE) studies were rated as rarely appropriate tests for infective endocarditis (IE) [5]. Over the past 15 years, there are 9 guidelines that cover IE diagnosis and contain evidence-based recommendations on the appropriate use of Echo (only in English language, and the latest version of updating guidelines).…”
Section: Introductionmentioning
confidence: 99%
“…Timely and accurate guidance should be available for the diagnosis and management of IE. As per a single-center study, a considerable number of transesophageal echocardiography (TEE) exams were rated as inappropriately used for IE [5]. Over the past 15 years, there have been 9 guidelines that cover IE diagnosis and contain evidence-based recommendations on the appropriate use of echo (all published in English, and the latest version of each guideline was considered).…”
Section: Introductionmentioning
confidence: 99%